2008
DOI: 10.1021/bi801925p
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban Thiols Play a Central Role in Activation of the Cardiac Muscle Sarcoplasmic Reticulum Calcium Pump by Nitroxyl

Abstract: Nitroxyl (HNO) donated by Angeli's salt activates uptake of Ca(2+) by the cardiac SR Ca(2+) pump (SERCA2a). To determine whether HNO achieves this by a direct interaction with SERCA2a or its regulatory protein, phospholamban (PLN), we measured its effects on SERCA2a activation (as reflected in dephosphorylation) using insect cell microsomes expressing SERCA2a with or without PLN (wild-type and Cys --> Ala mutant). The results show that activation of SERCA2a dephosphorylation by HNO is PLN-dependent and that PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 17 publications
8
90
0
2
Order By: Relevance
“…2) show some important features: (i) PLN R9C pentamers have slightly less mobility than the PLN wt , which suggests a change in the protein structural topology (i.e., hydrodynamic radius), and (ii) the presence of heat-resistant dimers. The latter was also observed in the oxidation studies of PLN wt carried out by Froehlich et al (34) (Fig. 2).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…2) show some important features: (i) PLN R9C pentamers have slightly less mobility than the PLN wt , which suggests a change in the protein structural topology (i.e., hydrodynamic radius), and (ii) the presence of heat-resistant dimers. The latter was also observed in the oxidation studies of PLN wt carried out by Froehlich et al (34) (Fig. 2).…”
Section: Resultssupporting
confidence: 71%
“…In vitro assays reported in the previous sections and work from other groups (26,34) (Fig. 4E), with approximately 5% increase in the emission of YFP-PLN R9C .…”
Section: Plnsupporting
confidence: 58%
See 1 more Smart Citation
“…However, recent evidence suggests an alternative, phosphorylation-independent mechanism of SERCA2a-regulated Ca 2þ reuptake. In fact, Froehlich et al (2008) showed that activation of SERCA2a could be achieved by modifying critical thiol residues in the PLN, which through protein conformation change relieves the inhibition of the pump. In particular, the covalent adduction of a nitroso group to a cysteine thiol side chain has recently emerged as a major mechanism by which NO mediates a large number of intracellular processes (Hess et al 2005) and an increase in proteins S-nitrosylation by NO was recently observed, also in eel cardiac tissues (Cerra et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that myocardial production of NO by eNOS and/or neuronal NOS may stimulate the activity of SERCA (7,28,51) by removing the inhibitory effect of phospholamban via nitrosylation of its cysteine residues (7). The role of NO on SERCA activity might explain the severe contracture attributable to L-NNA administration, when also the basal release of NO is impaired if not prevented.…”
Section: Is No Involved In Ap-postc Protection?mentioning
confidence: 99%